2020
DOI: 10.3390/land9050140
|View full text |Cite
|
Sign up to set email alerts
|

Airflow Field Around Hippophae rhamnoides in Alpine Semi-Arid Desert

Abstract: The research on wind regimes and the wind protection mechanism of sand-fixing plants has mainly relied on wind tunnel experiments; few observations have been made in the field. At the same time, airflow around individual standing vegetation elements and communities is relatively lacking in alpine semi-arid deserts. Therefore, this paper selected 10-year-old Hippophae rhamnoides (sea buckthorn) on sandy land on the eastern shore of Qinghai Lake as the study object. Based on spatial and temporal changes of wind … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Before artificial measures were taken, sand movements were extremely strong on mobile dunes because of forceful winds in winter and spring. Once plantations were established on dunes, wind-related hazards decreased considerably (Tian et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Before artificial measures were taken, sand movements were extremely strong on mobile dunes because of forceful winds in winter and spring. Once plantations were established on dunes, wind-related hazards decreased considerably (Tian et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The WPSER is a low-wind energy environment whose aeolian activity is strongest from late autumn to early spring, being controlled by the north-west wind direction. The threshold wind velocity for sand movement on a mobile dune is 6.5 m s −1 , but it is greater than 8 m s −1 on afforestation dunes (Tian et al, 2020). The natural shrub species distributed in natural fixed dunes are mainly Artemisia ordosica and Caragana jubata, while natural herbs are Carex qinghaiensis and Achnatherum splendens.…”
Section: Study Areamentioning
confidence: 95%
See 2 more Smart Citations
“…Tian et al [28] found that Hippophae rhamnoides has a significant windproof function in the Qinghai-Tibet Plateau, with a suitable Hippophae rhamnoides spacing density of 1.5 m for alpine desert control projects. Li et al [29] demonstrated that the artificial forests of Populus cathayana in the northeastern part of the Qinghai-Tibet Plateau contribute to the stability and ecological restoration of the Mugetan Desert, where a 30-year-old artificial forest can form a moss crust on the surface of the sand dunes, thereby stabilizing them.…”
Section: Introductionmentioning
confidence: 99%